2015
DOI: 10.4103/0975-7406.168019
|View full text |Cite
|
Sign up to set email alerts
|

Development of standard operating procedure and standardization of Habb-e-Banafsha Qawi-A Unani polyherbal formulation

Abstract: Introduction:Herbals drugs became a boon for mankind since ancient times and still are used worldwide for the treatment of various human ailments. The safety of alternative medicinal preparations has been questioned due to reports of unwanted side effects. To maintain the quality and efficacy of these drugs, it is essential to standardize them in order to avoid the use of substandard or adulterated medicines in the market. Unani system of medicine mainly focuses on the treatment by natural drugs. Habb-e-Banafs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Also Ali et al developed a poly-herbal formulation named Habb-e-Banafsha Qawi which could be useful in cough and coryza. 22 A new wound healing agent using marine biomaterials (squid ink polysaccharide) and chitosan as a carrier and CaCl2 to initiate coagulation also prepared by Huang et al and they concluded that this system provides rapid hemostasis and protects from wound infection. 23 One of the natural marine compounds that has antacid property is cuttlebone (CB) that contains a large amount of CaCO3.…”
Section: Discussionmentioning
confidence: 99%
“…Also Ali et al developed a poly-herbal formulation named Habb-e-Banafsha Qawi which could be useful in cough and coryza. 22 A new wound healing agent using marine biomaterials (squid ink polysaccharide) and chitosan as a carrier and CaCl2 to initiate coagulation also prepared by Huang et al and they concluded that this system provides rapid hemostasis and protects from wound infection. 23 One of the natural marine compounds that has antacid property is cuttlebone (CB) that contains a large amount of CaCO3.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of SOPs (Standard Operating Procedure): Despite the rising research and acceptance of the field of TM, certain studies are reporting adverse health effects of TM, this may be due to the variable quality, efficacy, and contents of herbal products as a class of medicinal products. In this regard, the development of SOPs for carrying out research studies based on TM could help generate evidence-based research data, also the data generated could be patented based on standard operating protocols used (9).…”
Section: Lack Of Research and Development In The Fieldmentioning
confidence: 99%
“…There is a lack of administrative policies specially made for traditional medicines. In Medical institutions, there should be a separate ethical committee and Dean for approval of doing Traditional medicine research (9). These committees should contain medical experts as well as people who are experts in traditional medicine.…”
Section: Lack Of Administrative Bodiesmentioning
confidence: 99%